Pembuatan Komik Literasi Informasi Untuk Meningkatkan Literasi Siswa di Perpustakaan SMA Negeri 1 Padang - Ilham, Muhammad; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe writing of this paper aims to explain the making of information literacy comics to increase student literacy in the Public Library of Padang 1 High School. The method used in this paper is descriptive method, the data is taken through field observations and interviews with librarians and librarians, based on facts that occur in the field of Public Library 1 Padang. Based on these results it can be concluded that the making of information literacy comics can be concluded the following steps. Determine the topic or theme of the Comic, Thinking of characters or extras, Determine the character to be played, Determine the setting of the place, Determine the setting of the atmosphere, Determine the setting, Determine the title, Make a title, Make a script, Provide tools and materials, Make a comic panel, Make a sketch of a picture comic characters, thickening comic character drawings, sketching conversation balloons, thickening panel lines, making storyline text columns according to narration, coloring sketch pictures on comics, thickening story conversation balloon lines, filling text in conversation bubbles and storyline columns in comics, Thicken the character image using a ballpoint pen. Keywords: comics, information literacy comics, student literacy